Internationalizing peace psychology - Christie, Daniel J.; Mohd. Noor, Noraini (Springer, 2011)
We describe the history, growth, and current scope of peace psychology, which is dominated by the security concerns of Western countries. Then we ask the question: How would the content and scope of peace psychology be different if more weight were given to the geohistorical issues, perspectives, and research agendas of scholars from Asia and developing parts of the world? We answer by suggesting that the emphasis in peace psychology would shift toward the problem of structural violence and the role of personal peace, religion, and emancipatory agendas in the pursuit of intergroup peace and social justice. We conclude with recommendations for future research in peace psychology, focusing mostly on the importance of increasing collaborative opportunities between the West and the rest of the world, in order to deal effectively with a wide range of conflicts as well as the global problem of ideological extremism.